Multi-criteria analysis of professional education on supply chain management - Tramarico, Claudemir Leif; Karpak, Birsen; Salomon, Valerio Antonio Pamplona; Silveira, Camila Aparecida Maciel Da; Marins, Fernando Augusto Silva (Associação Brasileira de Engenharia de Produção, 2019)
AbstractPaper aims This paper presents an analysis of professional education programs on Supply Chain Management (SCM). The purpose of this study is to analyze six professional education programs offered by the leading SCM associations, including Advanced Certified Professional Forecaster, Certified Production and Inventory Management, Certified Professional in Supply Management, and Supply Chain Professional. The analysis of professional education programs shall consider relevant criteria. There are multiple relevant criteria; some are tangible, and some others are intangible.Originality In 2007 Prof. Lummus researched professional education influence to SCM practices. This work is an extension of Prof. Lummus research, updating it, including more professional education programs and analyzing with AHP.Research method This paper applied the Analytic Hierarchy Process (AHP), a method for multi-criteria analysis, considering individual benefits and organizational benefits as the two main criteria, and professional education programs as alternatives.Main findings The two major contributions of this paper are: first, it presents individual benefits and organizational benefits that must be met by professional education programs; second, it evaluates the programs from multiple perspectives.Implications for theory and practice The approach proposed evaluates both tangible and intangible benefits of the programs.
Keywords: Analytic hierarchy process; Professional education; Supply chain management